Chemo-geographical variations in volatile profiles and antifungal properties of essential oils from Iranian Mentha longifolia L. populations - Neda Mokhtari; Vahid Abdoosi; Vahid Zarrinnia; Ali Mehrafarin (Journal of Biological Research, 2025)
Mentha longifolia L. is one of the most important species of the Lamiaceae family, consisting of seven varieties in Iranica flora. This herb has been used as a traditional medicine for a long time. There are many studies on the identification and correlation between this species and environmental factors. The first part of this research was designed for determinate the Essential Oil (EO) composition of M. longifolia growing wild in the north-west of Iran. A total of twenty compounds have been identified, accounting for 92.82–100% of the total oil composition through the HPLC method. Results have shown that the major components of the oil and their percentages were pulegone (7.18-52.23%), menthone (10.18-32.54%), and piperitenone oxide (0.77-16.01%). In addition, the essential oil showed strong levels of antifungal activity against the tested microorganisms: Botrytis cinerea, Penicillium sp., and Rhizopus stolonifera. At a similarity of 50%, the essential oil properties were divided into 2 sub-clusters, including cluster I, which contained mainly 6 ecotypes, and cluster II, which included 2 ecotypes. In addition, minimal inhibitory concentration for fungi growth revealed 2 main clusters consisting of 3 and 4 ecotype groups.